2018
DOI: 10.1007/s10811-018-1657-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foresting barren ground with Macrocystis pyrifera (Linnaeus) C. Agardh on the occurrence of coastal fishes off northern Chile

Abstract: Macrocystis pyrifera kelp beds play a significant ecological role along the coast of Chile. Besides their importance as food, protection structures, substrata, microhabitats and nurseries, regularly occurring natural disturbances (e.g. extremes of the climate variability El Niño-Southern Oscillation) and increased kelp exploitation affect these habitats. The present study aimed to test the dependence of reef fishes on Macrocystis pyrifera and to evaluate the effect of an enhanced habitat structure (experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 91 publications
1
10
1
Order By: Relevance
“…Fish assemblages observed here were composed of typical species from the Chilean coast. The comparatively low total number of fish species per site was similar to SR of reef-fish observed by other studies along the central and northern coast of Chile (Gelcich et al, 2008; Ory et al, 2012; Villegas et al, 2018). Pérez-Matus et al (2007) studied the structure of fish assemblages in northern Chile and found that CA was the site with the highest SR.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Fish assemblages observed here were composed of typical species from the Chilean coast. The comparatively low total number of fish species per site was similar to SR of reef-fish observed by other studies along the central and northern coast of Chile (Gelcich et al, 2008; Ory et al, 2012; Villegas et al, 2018). Pérez-Matus et al (2007) studied the structure of fish assemblages in northern Chile and found that CA was the site with the highest SR.…”
Section: Discussionsupporting
confidence: 87%
“…These species are common in northern Chile and display variable colour patterns (Méndez-Abarca & Mundaca, 2016), making it sometimes difficult to distinguish among them, especially in videos with limited visibility. As both species are of similar size and ecological habits, we treated them as Scartichthys viridis/gigas (see also Villegas et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Villegas et al. ). Kelps are also sensitive to human activities, such as changes in water quality (Vergés et al.…”
mentioning
confidence: 96%
“…In many systems, kelp beds alter water flow and provide important habitats for adult and juvenile fish by increasing structural complexity that offers refuge from predators and production of fish prey (Wharton and Mann 1981;Duggins 1988;Holbrook et al 1990;Norderhaug et al 2005). Kelp can be a major driver of patterns in fish and zooplankton presence (Holbrook et al 1990;Villegas et al 2019). Kelps are also sensitive to human activities, such as changes in water quality (Vergés et al 2016) or predator removals that cause trophic cascades (Estes and Palmisano 1974).…”
mentioning
confidence: 99%